The Golden Shovel Anthology : New Poems Honoring Gwendolyn Brooks - Brooks, Gwendolyn, 1917-2000; Brooks, Gwendolyn, 1917-2000; Hayes, Terrance; Smith, Patricia, 1955-; Shankar, Ravi, 1975-; Kahn, Peter (Peter R.) (Book collections on Project MUSE., 2017)
"The last words of each line in a Golden Shovel poem are, in order, words from a line or lines taken from a Brooks poem. The poems are, in a way, secretly encoded to enable both a horizontal reading of the new poem and vertical reading down the right-hand margin of Brooks's original. An array of writers, including Pulitzer Prize winners, T. S. Eliot Prize winners, National Book Award winners, and National Poet Laureates, have written poems for this anthology: Rita Dove, Billy Collins, Nikki Giovani, Sharon Olds, Tracy K. Smith, Mark Doty, Sharon Draper, and Julia Glass are just a few of the contributing poets." --